If y = cosh(log x) + sinh(log x), prove that...
Understand the Problem
This question requires us to prove a relationship given the definition y = cosh(log x) + sinh(log x). We would need to differentiate 'y' with respect to 'x' (likely twice) and then manipulate the resulting expressions to arrive at the desired proof, which seems to be cut off in this question.
Answer
$x$
Answer for screen readers
$x$
Steps to Solve
- Express y in terms of exponentials
Recall the definitions of $\cosh(u)$ and $\sinh(u)$: $\cosh(u) = \frac{e^u + e^{-u}}{2}$ and $\sinh(u) = \frac{e^u - e^{-u}}{2}$
Substitute $u = \log x$: $y = \cosh(\log x) + \sinh(\log x) = \frac{e^{\log x} + e^{-\log x}}{2} + \frac{e^{\log x} - e^{-\log x}}{2}$
- Simplify the expression for y
Simplify the expression by combining like terms: $y = \frac{e^{\log x} + e^{-\log x} + e^{\log x} - e^{-\log x}}{2} = \frac{2e^{\log x}}{2} = e^{\log x} = x$
- Differentiate y with respect to x (first derivative)
Differentiate $y = x$ with respect to $x$: $\frac{dy}{dx} = 1$
- Differentiate again with respect to x (second derivative)
Differentiate $\frac{dy}{dx} = 1$ with respect to $x$: $\frac{d^2y}{dx^2} = 0$
- Deduce the solution / Conclusion Given that $\frac{d^2y}{dx^2} = 0$, and $\frac{dy}{dx} = 1$, we can say any expression based on these values can be found. Since the question is cut off we can assume that we have to find the value for the expression: $x^2 \frac{d^2y}{dx^2} + x \frac{dy}{dx}$. $x^2 (0) + x (1) = x$.
$x$
More Information
The expression simplifies nicely because of the properties of hyperbolic functions and logarithms!
Tips
Null
AI-generated content may contain errors. Please verify critical information